PENGGUNAAN ALGORITMA SELECTION SORT UNTUK MENENTUKAN NILAI TERTINGGI SISWA - Farah Aura D.E.; Dwi Otik (Universitas Katolik Musi Charitas, 2023)
Data sorting is a type of operation that is quite important in data management. In daily life, we often encounter problems that need to be sorted by involving data sorting operations. Sorting operations are very important, so data sorting methods have been developed. The data sorting programming process is a much-needed process. Sorting is the process of sorting, organizing an object in a certain order or with a certain arrangement. The purpose of sorting data is to simplify the data search process when needed. In giving a student a sorting needs to be done. So, the teacher can easily determine or sort the grades of each student. Sorting grades or data must have been done frequently, in the field of education. In doing sorting usually on students requires a short time and long enough. Because of the large number of students in a school. In this case we can utilize an algorithm to make it easier to sort the data. The selection sort algorithm is an algorithm that can be used in sorting data. The selection sort algorithm can be used for sorting values or data, from maximum to minimum data or vice versa can be done with this method. By using the selection sort algorithm, it is hoped that it can lighten and simplify the teacher's work in order to sort student grades so that later the highest score of students in the school will be obtained.